The place behind the case: leptospirosis risks and associated environmental conditions in a flood-related outbreak in Rio de Janeiro O lugar do caso: leptospirose e riscos associados a condições ambientais durante o surto de 1996 na Zona Oeste do Rio de Janeiro - Christovam Barcellos; Paulo Chagastelles Sabroza (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2001)
The environmental context in which a leptospirosis outbreak took place during the summer of 1996 in the Rio de Janeiro Western Region was examined by using spatial analysis of leptospirosis cases merged with socio-demographic data using Geographic Information System (GIS). Risk areas were mapped based on flood and solid waste accumulation information for the region. Incidence rates were calculated for each area by the division of number of cases per total population in the specific areas. Higher rates were observed for census tracts inside the flood risk area and in the vicinities of waste accumulation sites. These findings are in agreement with the expected risk of leptospirosis, evidencing the role of environmental and collective factors in the determination of the disease. Neste trabalho foi averiguado o contexto ambiental do surto de leptospirose ocorrido no verão de 1996, na Zona Oeste do Rio de Janeiro, utilizando-se o Sistema de Informações Geográficas (SIG). As áreas de risco foram estabelecidas segundo o mapeamento das regiões sujeitas à inundação e de zonas em que há acumulação de lixo doméstico. Foram calculadas taxas de incidência da doença pela razão entre o número de casos e a população total em cada uma dessas áreas. Maiores taxas de incidência foram verificadas dentro da região sujeita à inundação e em torno daquelas de acumulação de lixo. Os resultados evidenciam o papel de fatores de risco ambientais e coletivos na determinação da doença.